APPLICATIONS OF THE RADON TRANSFORM TO REPRESENTATIONS OF SEMISIMPLE LIE GROUPS - Helgason, Sigurdur (1969)
From the point of view of the duality between points and horocycles in a symmetric space, the counterparts to the spherical functions on the symmetric space are the conical distributions on the manifold of horocycles. While the conical functions are closely related to certain finite-dimensional representations of semisimple Lie groups, in the present work the conical distributions are found to play various roles in the principal series of infinitedimensional representations of these groups.